Case Studies in Superconducting Magnets Design and Operational Issues - Iwasa, Yukikazu; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Case Studies in Superconducting Magnets, Second Edition, is intended for graduate students as well as professional engineers, and covers the basic design and operational issues of superconducting magnet technology. Based principally on magnet projects, chiefly of high-field DC solenoidal magnets, at the Francis Bitter Magnet Laboratory at the Massachusetts Institute of Technology, this book covers important and relevant topics on magnet design and operation issues: field distribution, magnets, force, thermal stability, dissipation, and protection. Features of the new edition include: New magnet design and operation issues primarily of high-temperature superconducting (HTS) magnets; Expanded coverage of field analysis, force analysis, cryogenics, AC losses, protection; Updated chapters throughout to reflect recent advances and new developments in the field; New homework problems and discussions; Fully updated references. Case Studies in Superconducting Magnets, Second Edition, serves as an important reference for magnet designers, experienced specialists as well as those just starting as professionals and as students, in the fields of mechanical, electrical, and cryogenic engineering.
SUPERCONDUCTING MAGNET TECHNOLOGY -- ELECTROMAGNETIC FIELDS -- MAGNETS, FIELDS, AND FORCES -- CRYOGENICS -- MAGNETIZATION -- STABILITY -- AC AND OTHER LOSSES -- PROTECTION -- SOLENOID EXAMPLES, HTS MAGNETS & CONCLUDING REMARKS.
Keywords: Engineering; Optics; Electrodynamics; Superconductivity; Superconductors; Magnetism; Magnetic materials; Mechanical engineering; Optical materials; Electronic materials; Engineering; Mechanical Engineering; Strongly Correlated Systems, Superconductivity; Magnetism, Magnetic Materials; Optical and Electronic Materials; Optics and Electrodynamics; Electronic books